2002
DOI: 10.1046/j.0007-1048.2001.03319.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the P15INK4b and P16INK4a in agnogenic myeloid metaplasia (AMM) and AMM in leukaemic transformation

Abstract: Summary. Hypermethylation of p15 and p16 genes was determined in 32 patients with agnogenic myeloid metaplasia(AMM), also known as idiopathic myelofibrosis (MF). These included 10 patients in leukaemic transformation phase. Using polymerase chain reaction‐based methylation analysis assay methods, with substantiation using Southern blot analysis, the study showed no hypermethylation of p15 or p16 genes in the chronic phase of AMM, but p15 gene hypermethylation was found in four patients (40%) and p16 gene hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
1
33
1
3
Order By: Relevance
“…Hypermethylation of the ABL1, CALCA, CDH1, CDKN4A, CDKN4B, DAPK1, MGMT, NPM1, TIMP2 and TP73 genes has been reported, albeit usually in low percentages of patients. [45][46][47][48][49][50] No methylation of TGFBR2 CpG islands was detected in PV or IMF. 51,52 Recently, Jost et al 45 reported methylation of SOCS1 in 15% of MPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of the ABL1, CALCA, CDH1, CDKN4A, CDKN4B, DAPK1, MGMT, NPM1, TIMP2 and TP73 genes has been reported, albeit usually in low percentages of patients. [45][46][47][48][49][50] No methylation of TGFBR2 CpG islands was detected in PV or IMF. 51,52 Recently, Jost et al 45 reported methylation of SOCS1 in 15% of MPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 In MPN, the mechanisms underlying progression to MDS and AML are poorly known, although hypermethylation of p15INK4b and p16INK4a genes has been described during the leukemic evolution of myeloid metaplasia. 8 The hypomethylating agent azacitidine has shown significant survival benefit in higher risk MDS. 9,10 In MPN, azacitidine appears to have limited efficacy in primary myelofibrosis (PMF) and myelofibrosis occurring during the evolution of essential thrombocythemia (ET) or polycythemia vera (PV) despite the induction of global hypomethylation.…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation of CpG islands causing inactivation of tumor suppressor genes has been seen in leukemic transformation of MF, 97 but rarely in "chronic phase" MF. 98 Decitabine is effective in MDS and has been used successfully in 1 sporadic case of chronic phase MF.…”
Section: Hypomethylating Agentsmentioning
confidence: 99%